Pecularities of the Change of Students – Prospective Teachers Atitude to Ethnic Music - Jautakytė, Rasa (Acta Paedagogica Vilnensia, 2003)
The article deal with the change of students attitude to ethnic music during a decade (1992-2002). The main role in bringing ethnic culture back to schools is played by the teacher and this role makes great demands on the teacher’s personality. Our long time observations proved that it is really important for students – prospective teachers to understand the significance of ethnic music for the development of the child and the child’s national self-consciousness. Analysis of the results of our experiment in 1992 and 2002 years brings us to the conclusion that an inadequate interest of students to ethnic music is determined by their scanty and episodic knowledge of national music, by their poor knowledge of the volume of folk songs. Comparative analysis disclosed, that although students seldom perform folk songs, their attitude towards ethnic music remains positive. Prospective teachers perceive the significance of teaching folk songs to children. That is why the majority of students chose folk songs, as a dominating element in their music lessons.